Resetting the ground fault relay on a 28 MVA power transformer due to grounding method retrofit - Hamzah, Eteruddin; Arlenny, -; Hadiana, Siswanto; Yanuar Z., Arief; Fathimah, Hasanti (IOP Publishing, 2022)
. The goal of the retrofit at Zamrud substation is to transform a 28 MVA power transformer's neutral point grounding system from direct grounding to grounding using a 20 Ohm Neutral Grounding Resistor (NGR). The amount of short-circuit current produced will fluctuate with the installation of NGR. It is necessary to re-setting the Ground Fault Relay (GFR) on Zamrud substation. To estimate the value of the short-circuit current after installing the NGR, the impedance matrix approach is used to calculate it. According to the results, LG's largest short-circuit current is 397.83 A and its smallest is 313.55 A. Meanwhile LLG has a maximum short-circuit current of 5.334.30 A and a minimum short-circuit current of 943.31 A. Therefore, after NGR installation, the value of the relay setting is as follows: GFR pickup current on the transformer grounding GFR relay is 234.29 A, GFR pickup current on the neutral feeder 1 is 19.96 A, GFR pickup current on the neutral feeder 2 is 30.42 A, and GFR pickup current on the neutral feeder 3 is 38.40 A.